The relationship amongst managerial overconfidence, audit committee, audit quality and material accounting misstatements / Nadiah Amirah Nor Azhari, Suhaily Hasnan and Zuraidah Mohd Sanusi - Nor Azhari, Nadiah Amirah; Hasnan, Suhaily; Mohd Sanusi, Zuraidah (Faculty of Accountancy, 2019)
The financial statement is the most important research tool available, especially to external users as they have limited access to a firm’s information. Prior accounting misstatement scandals shown that they have caused people to lose their jobs and in the context of financial reporting, losses to investors who make economic decisions based on misstated information; thus, research has been conducted to eradicate this issue. This paper discusses the relationships between managerial overconfidence, financial distress, audit committee, CEO duality and audit quality and the occurrence of material accounting misstatements by Malaysian listed companies. Managerial overconfidence and financial distress are viewed as motives for accounting misstatements in this study. Audit committee characteristics, i.e., independence and expertise of its members, CEO duality and audit quality are viewed as the ‘loopholes’ in corporate governance mechanisms that provide opportunities for proprietors to issue accounting misstatements. The sample for this study consists of 237 Malaysian listed companies, which includes data from misstated company reports with its respective matched data of non-misstated company reports. The results of this study show that financial distress and CEO duality are significantly related to the occurrence of accounting misstatements. This paper contributes to the body of knowledge on how to mitigate accounting misstatements, especially with the inclusion of the managerial overconfidence variable, which is a new addition to the research on accounting misstatements in Malaysia.